Building Better Clinical Relationships With Patients: An Argument for Digital Health Solutions With Black Men - Ledric D Sherman; Stuart W Grande (SAGE Publishing, 2019)
There is a rapid evolution of care delivery taking place across the globe in response to an explosion of novel health technologies. Growing in parallel to this expansion is the anticipation of mHealth technologies to drive patient-centered care into the future. Despite this hope, continuing reports of health inequities and lived experiences of substandard care fill national, state, and community health reports. The impact of these inequities is particularly pernicious on Black men and their long-term health status. As decades of robust evidence substantiates needed interventions, current progress is not seeing expected gains. In this commentary, we argue that at the heart of these inequities are issues of access, health literacy, institutional racism, and growing social distance between clinicians and Black men. To address these inequities, we suggest that digital interventions, designed to support decision-making, information exchange, and shared accountability have the best hope to overcome current inequities by promoting authentic relationships that ultimately drive better communication between Black men and their clinicians.